2009
DOI: 10.1021/ma901174r
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Healing through Supramolecular Cross-Links

Abstract: The ability of highly cross-linked thermoset materials to relax stresses by network chain segment mobility above or just below T g is generally limited. We describe materials in which some of the crosslinks have been replaced by dimers of quadruple hydrogen-bonding ureidopyrimidinone (UPy) moieties, which act as reversible cross-links. Materials based on mixtures of ε-caprolactone and L-lactic acid, and containing different ratios of covalent and UPy dimer cross-links, were synthesized, and their thermal and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 23 publications
3
72
1
Order By: Relevance
“…4,5 In fact, selfhealing is currently one of the most active topics in materials science. [6][7][8] For polymers [9][10][11] and polymer coatings [12][13][14][15] several approaches have been reported to restore the integrity of the material, either by refilling the damaged areas, e.g., a) Electronic addresses: a.c.c.esteves@tue.nl and g.dewith@tue.nl via encapsulated reactive components (autonomous healing) or by reestablishing chemical bonds through reversible reactions triggered by external stimuli such as temperature, light or a pH switch (triggered healing). These approaches can use intrinsic healing concepts, [16][17][18][19] in which the healing agent is inherent to the material (i.e., is a part of the network or formulation) or extrinsic healing, where external components are added, such as filled capsules [20][21][22][23] or microvascular networks.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In fact, selfhealing is currently one of the most active topics in materials science. [6][7][8] For polymers [9][10][11] and polymer coatings [12][13][14][15] several approaches have been reported to restore the integrity of the material, either by refilling the damaged areas, e.g., a) Electronic addresses: a.c.c.esteves@tue.nl and g.dewith@tue.nl via encapsulated reactive components (autonomous healing) or by reestablishing chemical bonds through reversible reactions triggered by external stimuli such as temperature, light or a pH switch (triggered healing). These approaches can use intrinsic healing concepts, [16][17][18][19] in which the healing agent is inherent to the material (i.e., is a part of the network or formulation) or extrinsic healing, where external components are added, such as filled capsules [20][21][22][23] or microvascular networks.…”
Section: Introductionmentioning
confidence: 99%
“…One way to address this issue is to introduce a self-healing mechanism, which has received wide interest both from academia and industry in the last decades. [23][24][25][26][27] For polymers and polymer coatings, most reported self-healing approaches, such as encapsulation, 28,29 reversible bonds/interactions [30][31][32][33][34][35][36][37][38][39][40][41][42] or deformation recovery 43,44 aim at repairing mechanical properties or material integrity. Much less attention has been paid to self-healing mechanisms aiming to recover surface functionalities.…”
Section: -8mentioning
confidence: 99%
“…However, there are a few studies on polymer networks having both covalent and MHB cross-linkages. 18, 19 Wietor et al partially replaced covalent urethane cross-linkages formed by the reaction of a trihydroxy-terminated three-armed flexible aliphatic polyester and diisocyanate to UPy-based multiple hydrogen bonds. They found that the incorporation of the UPy units improves the mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the incorporation of the UPy units improves the mechanical strength. 18 However, it is not explored whether this strategy is applicable to high-performance thermosetting resins.…”
Section: Introductionmentioning
confidence: 99%